(untitled) (Proceedings of Faculty of Civil Engineering, 2023)
A beam model is experimentally subjected to multiple support seismic excitation and in parallel, a numerical model for simulation of this problem is developed. The goal is to better understand the behaviour of long slender structures subjected to multiple support excitation based on analyses of experimental results, and to validate the numerical model using experimental results. In this paper the effect of the number of added masses to the dynamic response and the beneficial (in this case) effect of the time delay of excitation between the supports to the displacements of the structure are presented.